Development of e-services with the implementation of microservice architecture – results of research in AMM Systems - Krzos, Grzegorz; Wojciechowska-Dzięcielak, Paulina; Krzos, Beata (Rozwój e-usług z implementacją architektury mikroserwisów – wyniki prac badawczych w AMM Systems, 2020)
The purpose of this article is to identify the management practices of the research and development project (R&D) in the field of e-services for residents, created by the IT company AMM Systems LTD – grantee of the RPOWD Programme 2014-2020, Measure 1.2.A. The article presents a preliminary pilot study, followed by an in-depth study among enterprises that have benefited from subsidies for the development of R&D activities. Manifold research questions were defined, i.e.: For what purpose did AMM undertake the development of research and development activities based on the selected research and development department? Were the products (i.e. e-services) carried out according to the plan? Do the developed e-services enhance the competitive advantage for AMM? The audited entity was AMM Systems LTD (formerly SISMS LTD). The subject of the research was the activity of the company and the activity of the R&D department implementing a R&D project co-financed by the EU
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 3 (57), s. 49-64
Keywords: e-service; microservice; mobile applications; R&D; AMM; aplikacja mobilna; B+R; e-usługa; mikroserwis